PENGARUH MODEL PBL (PROBLEM BASED LEARNING) TERHADAP KEMAMPUAN LITERASI MATEMATIKA PADA POKOK BAHASAN STATISTIK SISWA KELAS XI TKR SMKN 3 BOJONEGORO - Junarti, Dr; Mayasari, Novi (IKIP PGRI Bojonegoro, 2022)
Abstract: The purpose of this study was to determine the effect of the PBL (Problem Based Learning) model on the ability of Mathematical Literacy on the subject of Statistics for class XI TKR SMKN 3 Bojonegoro students. This type of research is a quasi-experimental research, because it is impossible in the study to control the relevant variables. This study used a posttest only control design. The population of all students of class XI TKR SMK Negeri 3. Cluster random sampling technique for sampling. The cluster random sampling technique is done by lottery. After the lottery, the results showed that class XI TKR 2 as the experimental class had 30 students and class XI TKR 1 as the control class had 30 students. Data collection techniques using interviews, tests and documentation. Before the questions are used, they are tested for validity, reliability, distinguishability, and level of difficulty. The data analysis technique used -t test. The results of the research. The t_count value obtained in the calculation using the Polled Variance formula is t_count = 2.0533, the significance level = 0.05 and the t_table price = 2.0017, so that the t_count> t_table value is obtained. Thus, it can be concluded that using the PBL (Problem Based Learning) model causes students to have better mathematical literacy skills than using the direct learning model on the subject of Statistics for class XI TKR SMKN 3 Bojonegoro students. Keywords: PBL; Mathematical Literacy Ability